Rancang Bangun Sistem Informasi Transaksi Berbasis Web Studi Kasus Kopi Bar Depok - William, Dewa; Sharyanto, Sharyanto; Whendasmoro, Raditya Galih (Journal of Engineering, Technology and Computing (JETCom), 2024)
Kopi Bar Depok is a café that still operates its business using a manual system. As a result, there are several issues, especially in the transaction process at this café. The medium used for transactions is still paper, and data is also stored in physical form, making it prone to damage and loss. Additionally, the transaction process takes a considerable amount of time and is inefficient. To address these issues in the transaction process at Kopi Bar Depok, a web-based Transaction Information System has been developed. This information system uses PHP as the programming language, MySQL as the database, and is created using the Waterfall method.